-36=18-6x
6x=36+18
6x=54
x=9
2007-01-08 09:11:04
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Hi There
To answer this question, you must understand the rule of moving from left to right and right to left of the equal side :
Additional will become Subtraction
Subtraction will become Addition
Multiplication will become Division and
Division will become Multiplication
(sorry, no short cut, you need to memorise there above)
and solve this equation will be easy
-36= 18-6x (bring -6x from rigth to left side)
-36+6x=18 (bring -36 from left to right side)
6x=18+36
6x=54 (bring 6 from left to right side)
x=54/6
x=9
2007-01-06 00:50:44
·
answer #2
·
answered by cls22cls 2
·
0⤊
0⤋
9
2007-01-05 20:58:21
·
answer #3
·
answered by Po-ey 1
·
0⤊
0⤋
9
2007-01-04 09:08:22
·
answer #4
·
answered by herbavoria 2
·
0⤊
0⤋
-36 = 18 - 6x
6x = 18+36
6x = 54
x = 9
2007-01-04 09:07:26
·
answer #5
·
answered by JasonM 7
·
0⤊
0⤋
-36=18-6x
-54= -6x (subtract 18)
x= 9 (divided by -6)
2007-01-04 09:08:38
·
answer #6
·
answered by 7
·
0⤊
0⤋
-36 = 18 - 6x
-36 - 18 = -6x
-54 = -6x
x = 9
2007-01-05 21:48:44
·
answer #7
·
answered by Fluffy 2
·
0⤊
0⤋
-36=18-6x
6x=18+36
6x=54
x=54÷6
x=9
just simple algebra
2007-01-04 09:24:56
·
answer #8
·
answered by "G" 1
·
0⤊
0⤋
...
- 36 = 18 - 6x
- 54 = -6x
6x = 54
x = 9
...
2007-01-04 09:25:40
·
answer #9
·
answered by Jon 3
·
0⤊
0⤋
-36=18(-6x)x2
X=0
2007-01-04 09:13:24
·
answer #10
·
answered by angrysandwichguy2000 3
·
0⤊
0⤋